Stress-Related Growth Among Transgender Women: Measurement, Correlates, and Insights for Clinical Interventions. Issue 10 (24th August 2022) - Antebi-Gruszka, Nadav; Cain, Demetria; Millar, Brett M.; Parsons, Jeffrey T.; Rendina, H. Jonathon
ABSTRACT: Although transgender women (TGW), and especially TGW of color, are disproportionately exposed to discrimination and violence, many of them experience stress-related growth. However, little is known about the experience of stress-related growth and its correlates among TGW. Using data from a racially-diverse sample of 210 TGW, the short version of the Stress-Related Growth Scale was modified to assess growth as a result of coming to terms with one's transgender identity among TGW. The psychometric properties of the modified scale were examined, along with its associations with various cognitive, emotional, and social factors. A confirmatory factor analysis revealed a unidimensional factor, along with excellent reliability. A stepwise regression revealed that positive reappraisal, internal locus of control, social support, and emotional expression were associated with greater stress-related growth. Findings suggest that cognitive, emotional, and social resources are related to stress-related growth in TGW. Interventions to foster stress-related growth among TGW are discussed.